From litigation to arbitration: promoting international commercial arbitration through Harmonisation in the East African community - Nakueira, Sophie (Centre for Law and Society, 2026)
Important scholarship argues that adopting modern arbitration laws is a necessary requirement for promoting a region as a suitable venue for holding international commercial arbitration and attracting Foreign Direct Investment. This thesis takes a next step. With its main focus on the East African Community, the thesis advocates the need for placing developing countries' dispute resolution mechanisms in the broader context of economic development. It argues that there is a need for legal reform of the old arbitration legislation in the region. Furthermore, it posits that adopting a uniform statute on international commercial arbitration is essential to achieving the economic goals of the East African Community.